America (the book) : a citizen's guide to democracy inaction. a citizen's guide to democracy inaction - Stewart, Jon, frey50; Karlin, Ben.; Javerbaum, David (New York, NY : Warner Books, 2004)
Offers tongue-in-cheek insight into American democracy.
Study guide - Foreword - Chapter 1 : Democracy before America - Chapter 2 : The founding of America - Chapter 3 : The President - Chapter 4 : Congress - Chapter 5 : The Judicial Branch - Chapter 6 : Campaigns and elections - Chapter 7 : The media - Chapter 8 : The future of Democracy - Chapter 9 : The rest fo the world - Afterword - Acknowledgments - Credits
Above title on cover: The Daily show with Jon Stewart presents.
The book is presented as a text book with discussion questions and classroom activities.
Keywords: United States -- Politics and government; United States -- History